Competition dynamics in Nigerian aviation industry: A game theoretic approach - Olatunji Abdul Shobande; Mobolaji Daniel Akinbomi (Future Business Journal, 2020)
Background: This paper develops a game theoretic model that analyses the dynamics of competition among the leading domestic aviation firms in the Nigerian aviation industry. It probes the abilities of the prisoner dilemma to describe the subjective behaviour of the firms, which provide a yardstick for assessing the optimal competitive strategies available to the firm to survive the business environment. Results: The solution of the game provides different optimal competitive strategies for the firms. While findings show that Aero Contractors placed more weight on flight pricing to survive in the industry, Arik Air needed to retain non-pricing competitive strategy to remain the leading domestic aviation firm in Nigeria. Conclusion: Based on our findings, we conclude that if both firms stick to the optimal strategy, they would both share the market.
Keywords: L2; L11; C69; C70; C71; 650; Firm strategy; Game theory; Duality; Aviation industry